1996
DOI: 10.1002/cjce.5450740410
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and optimization of cellulose and styrene graft copolymerization process

Abstract: Graft polymerization of styrene into cellulose was investigated using Ceric ions redox systems as initiator. A mathematical model with the D‐optimal design combined with the least squares method was applied to the system. The variables considered in the model are the reactant variables i.e. monomer and initiator concentrations and the processing variables i.e. reaction time, temperature and agitation rate. The optimal composition and processing conditions were determined using a three dimensional space analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The optimum value, a,, = 4.9 x los g/mol, calculated from the model taking into account the compromise optimum for yield and conversion output (Bataille et al, 1996) was confirmed by experiment (M,, =3.64 x lo5 g/mol). The corresponding values of composition and processing conditions which yielded the highest value of molar mass for grafted polymer were: V, = 3.44 g, V2 = 0.53 g, V3 = 10 mL, The more complicated task to search for the "best" compatibilizer requires the development of a flexible scheme of copolymer production depending on characteristics of its components.…”
Section: (4)mentioning
confidence: 53%
See 2 more Smart Citations
“…The optimum value, a,, = 4.9 x los g/mol, calculated from the model taking into account the compromise optimum for yield and conversion output (Bataille et al, 1996) was confirmed by experiment (M,, =3.64 x lo5 g/mol). The corresponding values of composition and processing conditions which yielded the highest value of molar mass for grafted polymer were: V, = 3.44 g, V2 = 0.53 g, V3 = 10 mL, The more complicated task to search for the "best" compatibilizer requires the development of a flexible scheme of copolymer production depending on characteristics of its components.…”
Section: (4)mentioning
confidence: 53%
“…The reaction was conducted under a nitrogen blanket essentially the same as was described elsewhere (Bataille et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After a series of washing steps using methanol (centrifuge), the obtained precipitate was filtered and rinsed with ethanol thrice to remove any unreacted L-lactide. After drying at room temperature overnight, the obtained material was dried in a vacuum oven at 60 o C for 6 h. Then, the monomer conversion degree was calculated by gravimetrical method [22,33], according to the Equation 1:…”
Section: Characterisation Of Grafted Cnfmentioning
confidence: 99%
“…[1] So far all types of polymerization reactions have been utilized to covalently attach polymer chains of defined structure onto specific positions of the cellulose moiety. Thus monomers such as styrene, [2] acrylic esters and -amides, [3] acrylonitrile, [4] ethylene oxide, [5] ethyleneimine, [6] e-caprolactam [7] and methyl methacrylate [8] have been successfully grafted by polymerization from the surface of cellulose.…”
Section: Introductionmentioning
confidence: 99%